2020
DOI: 10.1097/nna.0000000000000908
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Preparedness Competencies Among Nurses

Abstract: OBJECTIVE The aim of this study was to examine current levels of self-reported professional emergency preparedness competence among nurses. In addition, relationships between nurse professional emergency preparedness competence, personal preparation for a disaster, and perceived likelihood of reporting to work after a disaster are examined. BACKGROUND Evidence suggests wide gaps in nurses' familiarity with the dimensions of professional emergency prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…The results of the present study also demonstrated that the highest level of EPIQ was related to the triage dimension (3.45). The results of other studies also confirm this finding [ 4 , 10 , 37 , 38 ]. The high level of familiarity with triage can be because triage concepts have traditionally been included in nursing education programs [ 43 ] and emergency nurses have good information about it because it is performed daily in Emergency Departments (EDs) and Emergency Medical Services (EMS) [ 10 ].…”
Section: Discussionsupporting
confidence: 82%
“…The results of the present study also demonstrated that the highest level of EPIQ was related to the triage dimension (3.45). The results of other studies also confirm this finding [ 4 , 10 , 37 , 38 ]. The high level of familiarity with triage can be because triage concepts have traditionally been included in nursing education programs [ 43 ] and emergency nurses have good information about it because it is performed daily in Emergency Departments (EDs) and Emergency Medical Services (EMS) [ 10 ].…”
Section: Discussionsupporting
confidence: 82%
“… 10 Another recent study reported that nurses with emergency preparedness competencies are more likely to have professional competence in disaster responses, maintain personal disaster preparedness, and report to work after a disaster. 11 …”
Section: Introductionmentioning
confidence: 99%
“…10 Another recent study reported that nurses with emergency preparedness competencies are more likely to have professional competence in disaster responses, maintain personal disaster preparedness, and report to work after a disaster. 11 One of the roles of community public health centers (PHCs) is to minimize the effects of disasters on the population. Despite nurses being primarily responsible for most (72.97%) PHC disaster programs, previous study results indicated that 50% of PHC nurses had low disaster preparedness.…”
Section: Introductionmentioning
confidence: 99%
“…The literature exploring the role of nursing in emergency planning identifies nursing core competencies that span the entire range of EPP, mitigation, response, and recovery. [28][29][30][31][32][33][34][35] Specific involvement of nurses in organizational emergency management planning is recommended for many reasons, including leveraging their skills and experience as well as for engagement and training purposes. 31,36 While the numbers are extremely small, bedside nurses reported feeling neutral about their importance in emergency preparedness efforts for their organization in much higher proportions than other personnel categories.…”
Section: Discussionmentioning
confidence: 99%